2013
DOI: 10.1007/s40266-013-0110-z
|View full text |Cite
|
Sign up to set email alerts
|

Different Risk-Increasing Drugs in Recurrent versus Single Fallers: Are Recurrent Fallers a Distinct Population?

Abstract: Known FRIDs, such as psychotropic drugs, also increase the risk of recurrent falls. However, we found four relatively new classes that showed significant association with recurrent falls. In part, these classes may act as markers of frailty and comorbidity, or they may reflect differences in the risk factors affecting the older, frailer population that tends to sustain recurrent falls. Further investigation is needed to elucidate causes and ways to prevent recurrent falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
36
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
11
36
3
1
Order By: Relevance
“…As fear of falling is a modifiable risk factor, preventive activities need to be introduced early on, and intervention strategies should take this risk factor into account, for example, by increasing knowledge on how to reduce falls (Austin et al, 2007). It is reported that use of certain medication, such as benzodiazepines and sedatives, is a significant risk factor for falls (Askari et al, 2013;Evans, 2003). Surprisingly, in the present study, this risk factor only applies to individuals with no fall history.…”
Section: Discussionmentioning
confidence: 55%
“…As fear of falling is a modifiable risk factor, preventive activities need to be introduced early on, and intervention strategies should take this risk factor into account, for example, by increasing knowledge on how to reduce falls (Austin et al, 2007). It is reported that use of certain medication, such as benzodiazepines and sedatives, is a significant risk factor for falls (Askari et al, 2013;Evans, 2003). Surprisingly, in the present study, this risk factor only applies to individuals with no fall history.…”
Section: Discussionmentioning
confidence: 55%
“…Besides typical FRIDs such as central nervous system (CNS)-acting agents (benzodiazepines, sedatives, hypnotics, antidepressants, and antipsychotic drugs), in recent years relatively new classes (eg, anti-Alzheimer’s agents, neurotoxic chemotherapeutic agents, and nasal preparations) were identified as having significant association with falls 57. Meanwhile, results of several sporadic cohort studies showed that the degree of medication-related fall risk was dependent on one or some of the following factors: drug pharmacokinetic and pharmacodynamic (PK/PD) properties (eg, elimination half-life, metabolic pathway, genetic polymorphism, risk rating of medications despite belonging to the same therapeutic class), and/or characteristics of medication use (eg, number of medications and drug–drug interactions [DDIs], dose strength, duration of medication use and time since stopping, medication change, prescribing appropriateness, and medication adherence).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs mainly due to their side effects; such as sedation, dizziness, postural disturbances, altered gait and balance, or impaired cognition and these drugs are usually called fall-risk-increasing drugs (FRIDs) 9 . Numerous studies have evaluated the association of medication use with the risk of falling in elderly patients [10][11][12] .…”
Section: Jfsf 93mentioning
confidence: 99%